2014
DOI: 10.1111/twec.12144
|View full text |Cite
|
Sign up to set email alerts
|

The Gravity Model and Trade Efficiency: A Stochastic Frontier Analysis of Eastern European Countries' Potential Trade

Abstract: The opening up process of the eastern European countries was marked by greater integration of foreign direct investment (FDI) with their western neigbouring countries.Using the single step maximum likelihood (ML) approach to stochastic frontier analysis (SFA), the location and variance determinants of FDI are estimated using the knowledge capital (KK) model framework. The findings, based on a panel of bilateral FDI stocks from 10 western to 10 eastern European countries over the 1996 to 2007 period, suggest FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 34 publications
2
51
1
1
Order By: Relevance
“…For the Baltic states and Ukraine, there are some publications on the base of gravity models like Byers, et al, 2000;Ravishankar, Stack,2014. The opening up process of the eastern European countries is characterised by an increasing degree of trade integration with their Western neighbouring countries (Ravishankar & Stack, 2014;Kepaptsoglou, et al 2010).The authors attempted to provide evidence on the effects of an economic and political union by studying the trade flows of the three Baltic countries of Estonia, Latvia and Lithuania after the breakup of the Soviet Union. They resulted that Baltic foreign trade was not only reduced significantly but also diverted to the members of the former Soviet Union.…”
Section: Methodsmentioning
confidence: 99%
“…For the Baltic states and Ukraine, there are some publications on the base of gravity models like Byers, et al, 2000;Ravishankar, Stack,2014. The opening up process of the eastern European countries is characterised by an increasing degree of trade integration with their Western neighbouring countries (Ravishankar & Stack, 2014;Kepaptsoglou, et al 2010).The authors attempted to provide evidence on the effects of an economic and political union by studying the trade flows of the three Baltic countries of Estonia, Latvia and Lithuania after the breakup of the Soviet Union. They resulted that Baltic foreign trade was not only reduced significantly but also diverted to the members of the former Soviet Union.…”
Section: Methodsmentioning
confidence: 99%
“…Crampon [21] firstly proposed the tourism gravity model based on Newton's law of gravitation, and held the opinion that tourism for a place depends on the population size and wealth of the tourism-generating region, the attraction of the destination, and the distance between the tourism-generating region and the destination. Scholars also support this opinion in their study of tourism demand [22,23], destination accessibility [16], and distance decay [24], and eastern European countries' potential trade [25]. The tourism gravity model is a typical paradigm to study distance decay in tourism and to analyze the corresponding influence factors.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of food security cooperation to ensure food security urgently needs to constantly improve methods, accurately judge the potential between countries, and put forward integrated development suggestions. In further method combing, it is found that the existing quantitative research on cooperation potential focused on agricultural product trade potential using index analysis [33,34], trade gravity model [35][36][37], and stochastic frontier gravity model [38][39][40]. The analysis of agricultural cooperation potential is mostly qualitative [41][42][43].…”
Section: Potential Index Of Food Security Cooperationmentioning
confidence: 99%